Kisspeptin Activates Ankrd 26 Gene Expression in Migrating Embryonic GnRH Neurons - Soga, Tomoko; Lim, Wei Ling; Khoo, Alan Soo-Beng; Parhar, Ishwar S. (Frontiers in Endocrinology, 2016)
Kisspeptin, a newly discovered neuropeptide regulates gonadotropin-releasing hormone (GnRH). Kisspeptins are a large RF-amide family of peptides. The kisspeptin coded by kiss1 gene is a 145-amino acid- protein that is cleaved to C-terminal peptide kisspeptin-10. G-protein coupled receptor 54 (GPR54) has been identified as a kisspeptin receptor, and it is expressed in GnRH neurons and in a variety of cancer cells. In this study, enhanced green fluorescent protein (EGFP) labelled GnRH cells with migratory properties, which express GPR54, served as a model to study the effects of kisspeptin on cell migration. We monitored EGFP–GnRH neuronal migration in brain slide culture of embryonic day 14 transgenic rat by live cell imaging system and studied the effects of kisspeptin-10 (1nM) treatment for 36h on GnRH migration. Furthermore to determine kisspeptin-induced molecular pathways related with apoptosis, and cytoskeletal changes during neuronal migration, we studied the expression levels of candidate genes in laser captured EGFP–GnRH neurons by real time PCR. We found that there was no change in the expression level of genes related to cell proliferation and apoptosis. The expression of ankyrin repeat domain-containing protein (ankrd) 26 in EGFP–GnRH neurons was up-regulated by the exposure to kisspeptin. These studies suggest that ankrd26 gene plays an unidentified role in regulating neuronal movement mediated by kisspeptin-GPR54 signaling, which could be a potential pathway to suppress cell migration.